DAMPAK PERUBAHAN SOSIAL KEAGAMAAN MASYARAKAT PETANI KELAPA SAWIT DI NAGARI GERAGAHAN KECAMATAN LUBUK BASUNG KABUPATEN AGAM (1999-2017) - Sri Novianti (UIN Imam Bonjol Padang, 2018)
Sometimes a muslim, when afflicted with calamity and hardship, is able to be patient to bear it. However, when he is tested with pleasures, sometimes he isunable to pass the test. Hence, the Almighty Allah will not just test a personwith something bad. Rather, He will also test us with something good. Thisarticle examined some aspects of social change by palm oil farmers and theircommunities on their economical, educational, and religional aspect atNagari Garagahan, Lubuk Basung Subdistrict, and how it may impact thepalm oil farmers and the communities against their socio-religious. The studyfound there are both positive and negative impacts on the activity of palm oilfarmers and the communities against their socio-religious change. However,the field research, historical based approach was used as a researchmethodology. The results of this study demonstrate there is an increase fromthe positive impact on their economical, educational, and building of mosque.In contrast, the negative impact of the palm oil farm activity made the farmersand communities forgot to fulfill their obligation among the obligations of theAlmighty Allah, such as prayers, fasts, zakah, hajj and so on, In brief, theseriousness of the communities in doing their activity as palm oil farmersunconsciously make them focused in seeking worldly things, rather thanpursuing their relationship with the Almighty Allah.